A Study on the Design of "Question Chain" in Senior High School English Reading Teaching Based on the Cultivation of Thinking Quality - Fan, Qin (International Journal of Social Sciences and Public Administration, 2024)
Cultivating students’ thinking quality is one of the most important teaching goals in English reading teaching. The use of "question chain" in reading class is one of the crucial factors to achieve this goal. Starting from the requirements of the English Curriculum Standards for Senior High School (2017 Edition, 2020 Revision) on the cultivation of thinking quality, this paper first analyzes the existing problems in the cultivation of thinking quality of senior high students in English reading teaching and then introduces the concept, design principles and design steps of “question chain”. This paper aims to provide suggestions for the design of “question chain” in order to improve the effectiveness of senior high school English reading teaching.